Cross-sectional and longitudinal associations between serum vitamin D and continuous metabolic syndrome score among children and adolescents: roles of levels of inflammation in peripheral blood - Yanyan Li; Zhuang Ma; Yan Li; Ting Xiong; Ziyang Zhang; Bingxuan Kong; Wenlong Lu; Xiu Zhao; Rongfei Zheng; Yuhan Tang; Ping Yao; Zhe Su; et al. (Nutrition & Metabolism)
Abstract Background Serum vitamin D deficiency is intricately linked to metabolic disorders, however, evidence on its association with continuous metabolic risk in children and adolescents remains insufficient. This study aims to elucidate the relationship between serum vitamin D levels and continuous metabolic risk. Methods The cross-sectional analysis involved 4490 participants aged 6 ~ 18, and the longitudinal investigation included 1398 individuals aged 6 ~ 12 years. Serum 25(OH)D concentrations were quantified using liquid chromatography-mass spectrometry. Continuous Metabolic syndrome risk score (CMSRS), incorporating waist, blood pressure, blood lipid levels, and glucose metabolism as four components, utilizes age- and gender-specific Z scores to evaluate metabolic risk. Restricted cubic splines (RCS) were used to visualize dose–response relationships and generalized linear models (GLM) were used to estimate potential associations. Mediation analysis was used to evaluate the mediating role of levels of Neutrophil-to-lymphocyte ratio (NLR). Results The RCS indicated a negative linear association between serum 25(OH)D levels and CMSRS (P-overall = 0.0066, P-nonlinear = 0.1393). GLM revealed that compared to Q1, with the quartiles of serum 25(OH)D concentrations increase, the β value ranged from 0.028 (95% CI: − 0.093, 0.037) to 0.001(95%CI: − 0.067, 0.069), and then to -0.074 (95%CI: -0.146, -0.003, P for trend = 0.0659). For every 10 ng/mL increase in serum 25(OH)D concentration corresponded to the β value change -0.058 (95%CI: -0.098, -0.017). This association was more pronounced in younger or overweight/obese individuals. Furthermore, in the longitudinal study, as the baseline quartile of serum 25(OH)D concentration increased, the estimated change of subsequent CMSRS indicated a decreasing trend, ranging from -0.085 (95%CI: -0.203, 0.032) to -0.166 (95%CI: − 0.285, − 0.046), and then to − 0.174 (95%CI: − 0.296, -0.053, P for trend = 0.0031). The mediating proportion of levels of NLR was 7.2%. Conclusions Higher serum 25(OH)D concentration is significantly associated with reduced CMSRS in children and adolescents, and adequate serum vitamin D levels play a prominent role in preventing long-term metabolic disorders, partly meditating by inflammation in peripheral blood.